Uji Coba E-LKPD Garis Singgung Persekutuan Luar pada Siswa dan Guru SMA IT Iqra’ Kota Bengkulu - Hanifah, Hanifah; Mardiana, Eli; Sulistio, M; Apriyanti, Peni (EDUPEDIA Publisher, 2025)
The government through the Ministry of Primary and Secondary Education (Kemendikdasmen) established the 2013 Curriculum (K-13) and the Independent Curriculum with the addition of deep learning methods starting from the 2025/2026 academic year. This policy encouraged schools to integrate technology into learning. Based on this, SMA IT IQRA’ Bengkulu City was selected as the site for implementing a Student Worksheet (LKPD) based on the APOS model assisted by GeoGebra on the topic of common external tangents. This selection was in line with the school’s mission to improve the quality of learning in order to achieve achievements at the local, national, and international levels. The training was conducted on May 23, 2025, in the computer laboratory involving 18 grade XI students and 6 mathematics teachers. The methods included an explanation of the APOS model, practice in using GeoGebra, distribution of digital worksheets, independent completion of worksheets, student presentations, and completion of response questionnaires. Teachers also received an additional teaching module to be further developed independently. The evaluation results showed that the students’ average response score was 4.08, categorized as very good. Students found it easier to understand concepts through GeoGebra visualization, were enthusiastic about completing the worksheets, and were able to present their work well. Teachers gained new insights into integrating technology into learning. The main obstacles were limited devices and initial experience in operating GeoGebra. Overall, the training was effective in improving students’ conceptual understanding, technical skills, and learning motivation. Further research was recommended to expand the development of APOS-based worksheets in other mathematics topics, involve more schools, and assess their impact on academic achievement longitudinally.